Pemberian Biskuit Tepung Ikan Teri dan Tepung Daun Kelor terhadap peningkatan kadar HB dan berat badan ibu hamil - Arini Arini; Iin Octaviana Hutagaol (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; indicators to see the degree of public health are seen from the Maternal Mortality Rate (MMR) and the Infant Mortality Rate (IMR). The purpose of analyzing the effect of anchovy meal (Stolephorus commersonii) and Moringa oleifera leaf meal on the increase in hemoglobin levels and body weight of pregnant women. Method; Sample determination was determined by purposive sampling with inclusion and exclusion criteria. The research design used experimental one-group pre and post-test. Result; shows that there is a relationship between giving biscuits formulated with anchovy and moringa on maternal weight gain during pregnancy, maternal HB and infant outcomes born to mothers with anemia. Conclusion; that there is an effect of giving biscuits that have been formulated with moringa with anchovies on maternal weight, HB and baby output